PERANCANGAN ANIMASI INTERAKTIF PENGENALAN HURUF DAN ANGKA MENGGUNAKAN MACROMEDIA FLASH 8 PADA TK ALAM DINIYAH - Nadya Tri Sonita; Jeprimansyah, Jeprimansyah; Etika Melsyah Putri; Edwin Anwar (Yayasan Nusantara Hasana Berdikari, 2025)
The learning process at Alam Diniyah Kindergarten is still carried out using conventional methods, such as using books and blackboards, so it tends to be monotonous and makes students lose focus and pay attention to the lesson. For this reason, interactive animation was chosen as a solution to make the learning process more interesting, fun, and easy to understand for children. In this study, the animation for recognizing letters and numbers was designed using Macromedia Flash 8 which is expected to make it easier for teachers to deliver learning materials, so that it can attract students' interest in learning. The features that will be provided in this application include material on recognizing letters and numbers equipped with images and sounds.